Analisis Adaptasi Praktik Manajemen Keuangan Syariah Pada UMKM Yang Dikelola Oleh Generasi Milenial Di Kota Palembang - Adila Misbahussururi; Gustina; Titin Hartini (CV. ITTC INDONESIA, 2025)
This study aims to analyze the adaptation of Islamic financial management practices among micro, small, and medium enterprises (MSMEs) managed by the millennial generation in Palembang City. Along with the growing awareness of sharia principles in economic activities, it is important to understand the extent to which millennial MSME actors apply Islamic financial concepts in managing their businesses. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation involving 10 millennial MSME actors engaged in the food and beverage, fashion, and service sectors. The findings indicate that while there is a basic understanding of Islamic financial principlessuch as the prohibition of riba (interest) and the importance of fairness in transactions the implementation remains limited due to a lack of practical Islamic financial literacy and restricted access to Islamic financial institutions. Active involvement from the government, Islamic financial institutions, and educational bodies is required to enhance understanding and accessibility of Islamic financial practices for millennial MSME actors in Palembang.